Marine Geology and Sand Resources of the Southern North Carolina Inner Shelf. Issue 9 (30th August 2022) - Conery, Ian; Walsh, John P.; Mallinson, David; Corbett, David R.
Abstract: Beach nourishment is a popular engineering-with-nature (EWN) strategy used globally for shoreline stabilization and coastal storm damage reduction. Large-scale projects require dredging from offshore sand borrow sources. However, suitable sands for nourishment are not ubiquitous offshore, especially in sediment-starved southern NC. In 2015, >300 nautical miles (555 km) of sub-bottom, sidescan, bathymetry and 38 cores/grabs were collected in data gaps offshore southern NC and interpreted for geologic horizons and potential nourishment-compatible sand thickness. In addition, hundreds of paleochannels were mapped and evaluated for fill patterns and resource potential. Various forms of hardbottom were delineated, sometimes in close proximity to sand resources. Results show high spatial variability in the distribution of beach-compatible sands across the southern NC shelf, where only a thin sand veneer is observed in many locations, although some regions contained continuous deposits exceeding 3 m. The thickest shoal deposits (>5 m) were observed offshore New Hanover County Region. Underlying strata and bathymetry appear to affect channel shape and distribution. Channels with acoustically transparent fill may be suitable as nourishment sources, yet many channels show complex and variable fill suggestive of tidal and estuarine environments. Seafloor reconnaissance data are valuable in preventing multi-use conflicts on the shelf as shelf areas are increasingly being explored for other functions (e.g, wind farms, oil/gas, fish habitat). These findings provide a useful starting point for coastal managers seeking sufficient offshore sediment resources for nourishment in response to future storm events and sea-level rise.